PENGISIAN JABATAN HAKIM MAHKAMAH KONSTITUSI BERDASARKAN KAJIAN TERHADAP KREDIBILITAS DAN INDEPENDENSI HAKIM - Alsyam Alsyam (Faculty of Law, Universitas Riau, 2023)
AbstractThe personal judges of the Constitutional Court are the main pillars for realizing the independence and impartiality of the Constitutional Court. The composition of the nine judges at the Constitutional Court of the Republic of Indonesia, proposed three people by each state institution namely the People's Representative Council (DPR), the President, and the Supreme Court (MA). The involvement of the three state institutions in the mechanism for filling the positions of Constitutional Justices has the potential to trigger a conflict of interest (especially in the DPR and the President) which has an impact on the credibility and independence of the appointed Constitutional Justices. The research is doctrinal research by conceptual approach and statute approach. Results study explains that the dynamics of politics in Indonesia do not mature so that the guardian of Constitutional Court judges is threatened. Therefore, to avoid this offense, it is necessary to form an ad hoc committee in the process of selecting candidate judges for the Constitutional Court as a form of implementing independence. AbstrakPersonal hakim Mahkamah Konstitusi merupakan pilar utama untuk mewujudkan independensi dan imparsialitas Mahkamah Konstitusi. Komposisi sembilan hakim pada Mahkamah Konstitusi Republik Indonesia, diajukan tiga orang oleh masing-masing lembaga negara yakni Dewan Perwakilan Rakyat (DPR), Presiden, dan Mahkamah Agung (MA). Keterlibatan ketiga lembaga negara tersebut dalam mekanisme pengisian jabatan hakim konstitusi, berpotensi akan memicu terjadi konflik kepentingan (terutama di DPR dan Presiden) yang berdampak pada kredibilitas dan independensi hakim konstitusi yang ditetapkan. Metode penelitian ini menggunakan penelitian hukum normatif (doctrinal research) dengan pendekatan analitis (conceptual approach), pendekatan undang-undang (statute approach). Hasil penelitian ini menjelaskan bahwa dinamika perpolitikan di Indonesia tidak kunjung dewasa sehingga terancamnya marwah hakim Mahkamah Konstitusi. Oleh sebab itu, menghindarkan ketersinggungan tersebut maka perlunya membentukan panitia ad hoc dalam proses pemilihan calon hakim Mahkamah Konstitusi sebagai bentuk implementasi independensi.